A case of cost estimation in an engineer-to-order company moving towards mass customisation. (1st January 2012) - Brunoe, Thomas Ditlev; Nielsen, Peter
Engineer-to-order companies have a tremendous product variety compared to mass produced or even mass customised products, implying high costs in both business and production processes. In recent years however some engineer-to-order companies have acknowledged the great potential in applying principles and methods from mass customisation to reduce the cost of variety, including modularisation, product configuration and process automation. This paper presents a case study of applying a statistical method for cost estimation for quotation purposes in an engineer-to-order environment, where cost estimation can be resource intensive and time consuming. The method finds cost critical parameters within a product family. The potential benefits from applying the method includes: simplifying the quotation process and reducing the resources needed to issue a quotation. However, due to the nature of the method consistent data quality and substantial historical data are required.